STATE EXTERNAL DEBT AS A SOURCE OF COVERAGE OF THE RUSSIAN FEDERATION BUDGET DEFICIT - D. Karandin (Вестник университета)
The article deals with the current state of the Russian Federation budget deficit and the level of its sources of financing, by means of which it is possible to compensate for it. We discuss several ways to cover the budget deficit, such as raising taxes, devaluation, privatization of state assets, as well as government borrowing on the domestic and foreign markets. As a result, it highlighted the most efficient source of budget deficit, taking into account the socio-political and economic consequences, affecting the country's economic situation.